15th AIAA/CEAS Aeroacoustics Conference (30th AIAA Aeroacoustics Conference) 2009
DOI: 10.2514/6.2009-3291
|View full text |Cite
|
Sign up to set email alerts
|

Fan Noise Prediction with Applications to Aircraft System Noise Assessment

Abstract: This paper describes an assessment of current fan noise prediction tools by comparing measured and predicted sideline acoustic levels from a benchmark fan noise wind tunnel test. Specifically, an empirical method and newly developed coupled computational approach are utilized to predict aft fan noise for a benchmark test configuration. Comparisons with sideline noise measurements are performed to assess the relative merits of the two approaches. The study identifies issues entailed in coupling the source and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…8,9,26 The current study addressed source specification issues for the case of rotor-stator interaction to illustrate changes in 2xBPF predictions when additional source content was included. Following previous statistical studies, 27 the influence of relative phase between source modes was also shown through numerical experimentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,26 The current study addressed source specification issues for the case of rotor-stator interaction to illustrate changes in 2xBPF predictions when additional source content was included. Following previous statistical studies, 27 the influence of relative phase between source modes was also shown through numerical experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…For situations in which the source pressure is available, this greatly simplifies the conversion to the required acoustic potential. Previously, 9 this information was obtained by using the LINFLUX 8,24 code to compute the rotor-stator interaction tones generated as a result of the mean perturbations in the fan rotor wake impinging on the stator. In this study, the acoustic potential source profiles were computed using various combinations of the measured source modes obtained from the aforementioned rotating rake.…”
Section: B Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrecchia et al (2003) utilized numerical simulation to capture the development process of rotor wakes. The noise source was separated into several components through numerical methods by Nark et al (2009) and Peters and Spakovszky (2012), and noise prediction was carried out. Cooper and Peake (2006) used the wake evolution and the quasi-3D strip method to develop an asymptotic technique and a new model for the wake interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The fan stage has 22 blades and 54 stator vanes in its baseline configuration. This configuration was chosen because of its use in previous studies 8,9,10 and the availability of measured acoustic data 6,7 for further model validation. The cross-section of the SDT test configuration is shown in Figure 2 with candidate inlet and aft acoustic liner locations shaded in green.…”
Section: Test Configurationmentioning
confidence: 99%